ANALISIS PENAWARAN DAN PERMINTAAN KREDIT SERTA IDENTIFIKASI PELUANG EKSPANSI PEMBIAYAAN KREDIT SEKTORAL DI WILAYAH KERJA KBI MALANG - Pasha (University of Merdeka Malang, 2009)
This research aimed to identify the factors of demand and banking loan offer in KBIMalang by using panel data. The estimation result showed that not optimal function of bankingintermediacy in KBI Malang was caused more by the lack of demand for credit than creditcrunch. While analysis using plot revealed credit worthiness had a conclusion that some certainsectors in KBI Malang tended to be unmarketable for credit/fund. On the contrary, in somesectors, there were potencies of credit/fund distribution. However, the research result wasaggregate so it did not reflect the characteristic of bank condition precisely and economiccondition individually.